EMOSI POSITIF MANUSIA PERSPEKTIF AL-QUR’AN DAN APLIKASINYA DALAM PENDIDIKAN - Miftah Ulya (STIU Al-Mujtama Pamekasan, 2019)
Abstract: Humans are unique creatures that have emotions. The emotions behind the actions and willingness are also closely intertwined with all the personalities that give color to the mood. Emotion is a biological and psychological state and a series of tendencies to act that exist in oneself almost in every human action. In the Qur'an, the phrase